Multicriteria support in the prioritization of resources in cartographic works: a study in databases - Yoshio Morita, Carlos; Lima Medeiros, Rafael (Seven Editora, 2023)
The objective of the present work is to evidence the usefulness of the multicriteria methods in the prioritization of resources in the production of cartographic information. For this, a systematic review of the literature in scientific databases was carried out in the period from 2007 to 2022. Concepts and procedures related to the characterization of scientific production on prioritization and multicriteria decision support methods were observed in the literature, examining the contributions of different countries, journals, authors and research trends. The analysis of the works showed a significant preponderance of the AHP and MCDA-C multicriteria methods. DOI: https://doi.org/10.56238/tfisdwv1-092